Drought Adaptation and Responses of Stipa krylovii Vary Among Different Regions: Evidence From Growth, Physiology, and RNA‐Seq Transcriptome Analysis - Ziqing Gong; Zehang Qu; Yulin Liu; Tao Wang; Baijie Fan; Anzhi Ren; Yubao Gao; Nianxi Zhao (Ecology and Evolution)
ABSTRACT In the context of global climate change, exploring how plant adaptation and responses to drought vary among different regions are crucial to understanding and predicting its geographic distribution. In this study, to explore the drought adaptation and responses of the dominant species in the semi‐arid Eurasian Steppes and their differences among the different regions in terms of growth, physiology, and RNA‐seq transcriptome, Stipa krylovii was chosen as the study material, and a seed source (three regions: eastern, middle, and western regions) × soil moisture treatment (three treatments: control, light drought, and heavy drought) two‐factor experiment was conducted. (1) Four growth traits for individuals from the western region were significantly lower than those from the other two regions. By Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analysis on gene expressions of individuals from each treatment, unique enriched pathways were found under heavy drought. (2) The decrease in the number of tillers with the increasing drought was much lower for individuals from the western region than those from the other two regions. The differentially expressed genes (DEGs) of individuals from the eastern, middle, and western regions between heavy drought versus control were 4887, 1900, and 4896. By KEGG functional enrichment analysis, individuals from the eastern and middle regions mainly regulated energy metabolism and metabolism of other amino acids; and those from the western region mainly regulated biosynthesis of other secondary metabolites and carbohydrate metabolism. (3) Clustering analysis based on gene expressions separated the western region from the other two regions under the same drought treatment. This study indicates that drought adaptation and responses of S. krylovii vary among different regions, especially between individuals from the western region and the other two regions. These findings are essential to understanding the adaptive evolution of population and germplasm resource protection for this important species.